An Analytical Approach to Resolution of Wto/Eu Bodies Involved In the Dispute Settlement Process: Resolving Trade Disputes in the European Union (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The present Union ofEurope or better known as European Union a Union of Member States of Europeencompassing Economic and Political Union (to an extent) comes throughMaastricht Treaty in 1992. The provisions of Maastricht treaty were muchwidened by later day treaties of Amsterdam, Nice and Lisbon. Europe has for thefirst time a Parliament of its own, a Monetary Union giving birth to Euro asCommon currency, European Central Bank, Fiscal consolidation and free movementof trade and services. This all is regulated by European Union Law, whichincludes Trade laws through directives and regulations monitored by EuropeanCommission. Trade disputes among member states are resolving through DisputeSettlement Board (DSB). The trade disputes can be put in three categories one amongmember states within EU, secondly dispute between Member state of EU and NonMember states and third dispute arising out of non EU investor and Member of EUwhere EU is signatory to multilateral treaty and provisions of which has beenviolated by Member state. EU dispute settlement mechanism is largely based onWTO provisions and provisions of GAAT. In this article a study has been done onthese disputes particularly where EU directives and Regulations are in conflictwith Constitutional and Local Law of Member states.